Tingkat Hardiness pada Mahasiswa dalam Menghadapi Pembelajaran Online Masa Pandemi - Cah Soniman Nitema Gea; Iyus Yosep; Udin Rosidin; Indra Maulana; Witdiawati Witdiawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the hardiness of 2018 Unpad Faculty of Nursing final-year students dealing with online learning during a pandemic. The research method used in this research is a quantitative descriptive method. The results showed that 108 students (70.6%) of FKep Unpad A'2018 had moderate hardiness. In conclusion, the resilience and hardiness of FKep Unpad A'2018 students are in the medium category. Keywords: Hardiness, Student, COVID-19 Pandemic, Online Learning